Hydrocarbon preservation conditions in Mesozoic–Paleozoic marine strata in the South Yellow Sea Basin - Jie Liang (Natural Gas Industry B, 2017)
In the South Yellow Sea Basin, Mesozoic–Paleozoic marine strata are generally well developed with large thickness, and they are characterized by multi-source and multi-stage hydrocarbon accumulation, providing a material basis for the formation of large-scale oil and gas fields. However, no substantial breakthrough has been made in this area. Based on previous research results, the complex tectonic pattern of this superimposed basin was formed by multi-stage tectonic movements and the favorable static conditions for hydrocarbon preservation were reworked or destroyed by later superimposition. Therefore, hydrocarbon preservation conditions are the key factors for restricting the breakthrough of marine oil and gas exploration in this area. In this paper, hydrocarbon preservation conditions of marine strata in the South Yellow Sea Basin were comprehensively analyzed from many aspects, such as tectonic movement, source conditions, caprock characteristics, magmatic activities, and hydrogeological and hydrogeochemical characteristics. It is indicated that the complex tectonic pattern of the South Yellow Sea Basin is resulted from tectonic events in multiple stages, and the development and evolution of regional source rocks are mainly controlled by two stages (i.e., the stable evolution stage of Mesozoic–Paleozoic marine basin and the Mesozoic–Cenozoic tectonic pattern transformation and basin formation stage), so the characteristics of differential oil and gas preservation are presented. Besides, better marine hydrocarbon preservation preconditions in this area are weaker tectonic reworking, development of high-quality thick source rocks, good vertical sealing capacity of caprocks, weaker magmatic activity and confined hydrogeological conditions. It is concluded that the Laoshan Uplift in the central part of the South Yellow Sea Basin is structurally stable with weaker faulting and magmatic activities, so it is better in oil and gas preservation conditions. Besides, several large-scale structural traps with good petroleum geological conditions and complete source–reservoir–caprock assemblages are developed in this area. Therefore, this area is the most promising region for Paleozoic marine oil and gas exploration in this basin.